2023
DOI: 10.48084/etasr.5446
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Effect of the Impactor Head Shape to the Induced Damage during Impact at Low Velocity for Composite Laminates

Abstract: The present paper presents an investigation and analysis study of the effect of the head shapes of the impactor on the damages observed during low-velocity impact on T700/Epoxy composite laminate. Two types of impactors were investigated: hemispherical and flat-face. A new criterion based on the LARC05 damage model was linked as a LARC_VUMAT subroutine to simulate the impact and explore the effects of the head form shape through a three-dimensional finite element model. To properly analyze the problem, the his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Important parameters of the impact events are the peak impact forces and bending, the duration of the impact event, the stresses and strains and the shape of the contact zone [21], which need to be additionally analyzed. Further research should be performed to quantify the defect position by modal shape analysis and to investigate other types of defects and the anisotropy caused by the location of glass layers in composite beams.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Important parameters of the impact events are the peak impact forces and bending, the duration of the impact event, the stresses and strains and the shape of the contact zone [21], which need to be additionally analyzed. Further research should be performed to quantify the defect position by modal shape analysis and to investigate other types of defects and the anisotropy caused by the location of glass layers in composite beams.…”
Section: Discussionmentioning
confidence: 99%
“…Impulse excitation is a popular technique for the diagnosis of various materials [20]. In [21], it is shown that the shape of the impactor head is an essential parameter on the low-velocity impact. The damage occurring in the composite plates is illustrated and analyzed for hemispherical and flat head shape hammer [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Better impact resistance was observed in laminates that had a higher areal density and more layers of nickel-coated carbon fiber veils, which resulted in a higher impact force and smaller damage area [14]. The shape of the impactor has a considerable effect on the extent of damage induced in composite laminates during impacts at low velocity [15]. A considerable reduction in computational costs was achieved by implementing the mass-scaling method in the numerical analysis of the impact response of semicylindrical woven composite shells [16].…”
Section: Introductionmentioning
confidence: 99%